Development of bio-char using non-direct firing system from oil palm frond and its chemical properties: article - Ab Hamid, Nurhafizah; Jaapar, Jefri; Musa, Mohibah (2019)
One of the vital research in this area is to locate another biomass feedstock for bio-char production since an investigation on this issue is basic in light of the fact that each country has different biomass that can used an alternative energy. There is copious measure of wastes generated from the oil palm plantation like oil palm frond (OPF) in Malaysia which greatly increased over the years are mostly left on the fields. This waste particularly can be utilizing as the feedstock in the context of the bio-char via non direct firing system. The aim of this research is to analyze the characteristics OPF as a feedstock for slow pyrolysis for production of bio-char via nondirect firing system under various temperature 400, 500 and 600⁰C and also to analyze the chemical properties of OPF biochar based on thermo-gravimetric analysis (TGA) for proximate analysis, CHNS/O analyzer for ultimate analysis and functional group using Fourier-Transform Infrared Spectroscopy (FTIR). The proximate analysis of raw material oil palm frond (OPF) have more volatile matter (VM) but less ash content (AC) and moisture content (MC) compared with bio-char produced at different temperature. The data of fixed carbon (FC) for OPF was lower than bio-char at 400⁰C but higher compared to bio-char at 500 and 600⁰C. the carbon content in OPF was less than the carbon content in bio-char produce at all three different temperatures. Meanwhile, the hydrogen, nitrogen, sulphur were high in OPF but less in biochar produced. Furthermore, the oxygen content in OPF was less than bio-char produced at 500⁰C but the oxygen content in OPF was high than the bio-char produced at 400 and 600⁰C. For FTIR analysis, the spectra began to disappear with the increasing pyrolysis temperature. This result was due to functional group have rupture and progressive carbonization. It can be concluded that bio-char that were produced from OPF feedstock have different trend of chemical properties depending on the temperature.